Circulating inhibitor bound elastase in patients with ankylosing spondylitis and rheumatoid arthritis and the influence of sulphasalazine treatment. Issue 1 (January 1988) - Feltelius, N; Hällgren, R
Abstract : The plasma concentration of granulocyte elastase in complex with alpha 1 proteinase inhibitor was determined in 42 patients with ankylosing spondylitis (AS) and 33 patients with rheumatoid arthritis (RA). Significantly raised levels of plasma elastase were found in patients with RA, whereas patients with AS had normal values. No correlation was seen between the elastase values and erythrocyte sedimentation rate (ESR), serum haptoglobin, immunoglobulins, or polymorphonuclear cell (PMN) count in either of the patient groups. A correlation was found between the Ritchie index and plasma elastase in patients with RA. After three months' treatment with sulphasalazine a clinical improvement was seen and this paralleled a reduction of the acute phase reaction in both patient groups. A reduction of the circulating elastase values was seen in the patients with RA, whereas no change was seen in patients with AS.